PENGARUH OVERINVESMENT TERHADAP KINERJA PERUSAHAAN YANG DIMODERASI HUTANG DAN DEVIDEN - Cakra Lathif Hestapermana; Suci Atinigsih (Jurnal Akuntansi dan Bisnis, 2026)
This study aims to analyze the effect of overinvestment on firm performance, with debt and dividends as moderating variables. Using a quantitative approach and secondary data from annual financial reports, the study covers 47 technology sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. Through purposive sampling, 27 companies were selected as the sample, resulting in a total of 96 observations. The data analysis techniques include descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA) using EViews 12 software. The results show that overinvestment has a negative effect on firm performance. Debt is found to moderate the effect of overinvestment on firm performance, while dividends do not moderate this relationship.